Safe Extubation of Patients with COVID-19 for Minimizing Aerosolized Droplets - Masayuki Akatsuka; Asami Yoshinaka; Hiroya Hagiwara; Shuji Yamamoto (SAGE Publishing, 2021)
Background: Healthcare workers must be protected during extubation of patients with coronavirus disease 2019 (COVID-19) owing to the presence of aerosolized droplets. Herein, we report a technique for extubating a patient with COVID-19 while minimizing aerosol dispersion. Case Report: We retrospectively identified a total of 79 patients admitted to our hospital from February 2020 to January 2021. Six of these patients were intubated for mechanical ventilation, 2 of whom had to be extubated. We prepared a clear vinyl sheet in the shape of a tent to place over the patient, and 2 staff members, both well experienced in airway management, stood outside the tent on either side of the patient. Before extubation, we confirmed that the patient's consciousness level was good and the patient had no distress by adjusting the dose of sedative drugs. After extubation, a surgical mask was placed on the patient's face. Conclusion: Our experience indicates that this method of extubation in a patient with COVID-19 could be safely implemented to protect healthcare workers.